The Pattern of Joko Widodo's Political Dynasty Practices - Novia Fatimatuzzahra; Dian Suluh Kusuma Dewi (Universitas Muhammadiyah Malang, 2021)
The political steps of President Joko Widodo's son (Gibran) and son-in-law (Bobby Nasution) have become the spotlight and a warm conversation in almost all levels of Indonesian society, especially in online media. This candidacy received many public responses because it was considered an excellent fit to take advantage of their father, Joko Widodo, which led to dynastic politics during the presidency. This research aims to discuss how the media discusses the patterns of political dynasties in Indonesia, especially in the era of Joko Widodo's leadership. Specifically, the purpose of this study is to determine the nomination of Gibran and Bobby, who are suspected of being a political dynasty through online media. This research uses a qualitative approach. Data collected through data mining is carried out with the NVIVO 12 Plus NCapture feature from local and foreign online news portals. The data is processed using NVIVO 12 Plus using manual coding with a qualitative approach and cross-tabulation method. This research indicates Jokowi's involvement in using his capacity as president in Gibran and Bobby's nomination in the 2020 Regional Election. The controversy that has arisen shows the public's negative perception of political dynasties.